Moral Education Of Students To Respond To Youth Determination - Uni Khoerotun Rizkiyah (Beginner: Journal of Teaching and Education Management, 2023)
This study uses a qualitative approach, so that the main instruments in this study are educators, students, schools. As for the instruments that the authors use in collecting data in the field in accordance with the object of discussion in this study, the authors make observations and documentation. The teacher has some responsibility for providing moral education, when the child is at school to the teacher at school. There is no need to look at the child from which family is bestowed. Teachers are the parents of both students at school. As parents at school, teachers should be responsible for the development of their students both in terms of cognitive, affective and psychomotor. What's more, the teacher is more focused on instilling moral education for students to stay away from juvenile delinquency which is basically usually done by teenagers the same age as students at MTs Darun Nahwi Singajaya. With regard to good morals or examples, Allah SWT has provided an overview of the morals of the Prophet Muhammad SAW. Because in life, a human being from birth always acts and acts, thinks, feels, feels and relates to other people